2002
DOI: 10.2224/sbp.2002.30.7.661
|View full text |Cite
|
Sign up to set email alerts
|

Coping Style and Three Psychological Measures Associated With Environmentally Responsible Behavior

Abstract: Questionnaires containing five multi-item 5-point scales were administered to 153 Japanese male and female undergraduates. Data of each of the scales were factor analyzed and, as a rule, items with a factor loading of .40 or over were selected. The scale for coping style produced three factors: avoidance, self-deceptive optimism and problem solving. Each of the other four scales produced one factor. Using the total score for each scale or factor, multiple regression analysis was applied to environmentally res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 25 publications
3
50
0
4
Order By: Relevance
“…In the present study, the "Environmentally Responsible Consumerism Scale" was prepared based on Iwata (2002), the "Voluntary Simplicity Lifestyle Scale" was prepared based on Iwata (2006), and the "Consumption Values Scale" was prepared based on Lin and Huang (2012). It is argued in some studies that those adopting novelty do not engage in environmentally responsible consumerism.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the present study, the "Environmentally Responsible Consumerism Scale" was prepared based on Iwata (2002), the "Voluntary Simplicity Lifestyle Scale" was prepared based on Iwata (2006), and the "Consumption Values Scale" was prepared based on Lin and Huang (2012). It is argued in some studies that those adopting novelty do not engage in environmentally responsible consumerism.…”
Section: Methodsmentioning
confidence: 97%
“…Cowles and Crosby (1986) argued that voluntary simplicity is composed of the dimensions of material simplicity, self-determination, and ecological awareness. Iwata (1997Iwata ( , 2002Iwata ( , 2006 suggested that voluntary simplicity lifestyle can be examined in three sub-dimensions: cautious attitudes in shopping, acceptance of self-sufficiency, and a desire for a voluntarily simplicity life. Ozgul (2011), on the other hand, stated that a voluntary simplicity lifestyle has four dimensions: product feature, material life, planned shopping, and selfsufficiency.…”
Section: Literature Review 21 Voluntary Simplicity Lifestylementioning
confidence: 99%
“…Bickerstaff and Walker, 2001;Teisl et al, 2002;Bamberg, 2003;Iwata, 2002) in consumer preferences and their consequent purchase for green products. Without public engagement (The public may play a role as purchasers and users of goods, as a voluntary recycler and as educators to encourage other in engaging green consumption), waste generation may keep growing.…”
Section: Methodsmentioning
confidence: 99%
“…It refers to a decreased level of consumption or to austere behaviors intended at diminishing the impact of human behavior on the availability and renewability of natural resources [18,19]. Frugal behaviors are antagonist to consumerism, the prevalent lifestyle of modern societies, especially of those in the industrialized world [20].…”
Section: Frugal Behaviorsmentioning
confidence: 99%
“…Frugal actions involve daily reduced-consumption actions as well as the type of items purchased, the activities individuals engage in, and the way wastes are discarded or disposed. A number of researchers [18][19][20][21] have created and administered instruments assessing frugal behaviors. Their results reveal that these behaviors correlate with diverse instances of sustainable lifestyles and also with a number of determinants of pro-environmental behaviors.…”
Section: Frugal Behaviorsmentioning
confidence: 99%